Taming the Beast - Chigudu, Daniel (PCD Journal, 2025)
The study challenges the prevailing belief that conflict in the Democratic Republic of Congo (DRC) is mainly driven by ethnicity, weak governance, or resource mismanagement. It argues instead that reccurring violence stems from deeper structural problems, such as economic deprivation, systemic institutional failure, and the influence of multifaceted geopolitical interests. Despite repeated peace agreements and interventions, the root causes remain unaddressed, allowing tensions to resurface quickly. Using qualitative research based on secondary data from government reports, international organisations, and expert academic studies, the findings show that conflict in the DRC is phenomenally complex in nature and raises persistent questions about why the DRC has not benefited from its sizable economic potential. This study calls for developing strategies related to inclusive economic development policies to provide an institutional framework, restoring operationalisation of these institutional challenges. It refrains from straightforward explanations relating to ethnicity or mismanagement of resources. It aims to inform policy recommendations about future interventions by underpinning the path to sustained peace and national development in similarly complex contexts.